Buffy, Ballads, and Bad Guys Who Sing : Music in the Worlds of Joss Whedon. - Leonard, Kendra Preston (Rowman & Littlefield Pub. Group, 2010)
When writer and director Joss Whedon created the character Buffy the Vampire Slayer, he could hardly have expected the resulting academic interest in his work. Yet almost six years after the end of Buffy on television, Buffy studies--and academic work on Whedon's expanding oeuvre--continue to grow. Now with three hugely popular television shows, Buffy the Vampire Slayer, Angel, and Firefly, and the film Serenity all available on DVD, scholars are evaluating countless aspects ofthe Whedon universe (or "Whedonverse"). Buffy, Ballads, and Bad Guys Who Sing: Music in the Worlds of Joss Whedon studie.